Induction of Labour at 40 Weeks May Reduce Likelihood of Caesarean Section - Saima Iqbal, Razia Bibi, Sadia Hanif, Aiman Mehtab, Nosheen, Nighat Afridi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Aim of current study is to determine either induction of labour at 40 weeks may reduce likelihood of cesarean section. Study Design: Controlled trial Place and Duration: Gynaecology and Obstetrics Department Combined Military Hospital Peshawar for the duration of six months from 1st Jan 2021 to 31st December 2021. Methods: Total 48 pregnant females of age 18-45 years were presented in this study. After receiving informed written consent, detailed demographic information about the enrolled cases; including age, parity, gestational age, level of education, and region of residence was collected. Frequency of cesarean section with respect to labour induction was calculated among all cases. SPSS 22.0 was used to analyze all data. Results: Among 48 cases, 28 (58.3%) had age 18-28 years, 15 (31.3%) patients had age 29-38 years and 5 (10.4%) cases had age >38 years. There were 26 (54.2%) patients with BMI <25kg/m2 and 22 (45.8%) with BMI >25kg/m2. There were 18 (37.5%) patients with gestational age 34-36 weeks, 16 (33.3%) patients with gestational age 37-38 weeks and 14 (29.2%) patients with gestational age 39-40 weeks. Frequency of cesarean section among all cases were 15 (31.3%) in which majority of the cases were from gestational age 34-36 weeks. There was no mortality found among mothers. Conclusion: In this study we found that labour induction at 40 weeks significantly reduce the frequency of cesarean section. There were benefits for the fetus and no increased risk of maternal death. Keywords: Pregnant patients, Labour Induction, C-section, Gestational age